Estudo das propriedades magnéticas nos compostos (YxR1-x)(VxCr1-x)O4 (R = Gd, Tb, Dy, Er e Yb) - Jesus, Ana Carla Batista de (2022)
In this work was studied of the structural and magnetic properties of non-magnetic ions (V and Y) doped RCrO4 (R = Gd, Tb, Dy, Er and Yb) compounds obtained by the coprecipitation method. X-ray diffraction (XRD) analyzes combined with Rietveld refinement confirm the formation of a single phase consistent with the zircon-type structure, tetragonal symmetry and I41/amd space group. The lattice parameter and in the unit cell volume changes as a function of both V and Y concentration. The Energy Dispersive X-Ray Spectroscopy (EDS) analyzes semiquantitatively shown that the concentrations are close to the nominal value. The T-dependent magnetic susceptibility measurements (x(T)) are characterized by thermal hysteresis below the transition temperature and an evident displacement of the maximum of x(T) with increasing doping concentration, characterizing a systematic decrease in temperatures 24 to 3 K for the V-doped samples and 24 to 9 K for the Y-doped samples. These results show that the R-O-Cr magnetic interaction takes an important role in determining the magnetic properties in these RCrO4 compounds. The Curie-Weiss temperatures indicate an antiferromagnetic order for the rare earth sublattice, ferromagnetic for the chromium sublattice and indicate that for RCrO4 compounds the magnetic interaction paths between R-O-Cr ions along the c-axis is dominant. Although there are different magnetic interactions in the RCrO4 compounds, the effects of frustration seem to be stabilized, since all samples presented f values close to 1. The magnetization measurements as a function of the applied magnetic field (MvsH) performed at T = 2 K displays a ferromagnetic character for the RCrO4 compounds, also showing a decrease in magnetization for the Y-doped samples. However, for the compounds with R = Yb is verified the appearance of an anomaly in the low field region except for the compound YbVO4.